Are the Malaysian students “unskilled” and “unaware”? - LIM HOCK-EAM; SIEW GOH YEOK (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to use a representative sample of Malaysian university students to quantify the prevalence of "unskilled and unaware" phenomena in the country. Lack of generic skills, i.e., being "unskilled," has been cited as a contributing factor to the graduate unemployment problem, which has persisted since the financial crisis of 1998. Still, graduate unemployment cannot be blamed on the "unskilled" alone. The presence of both "unskilled" and "unaware" may be to blame.Methodology: Information is collected through interviews with students and faculty at Universiti Utara Malaysia’s Bachelor of Banking program. The questionnaire served as a data collection tool, with answers submitted by students before interviews and by interviewers afterward. Findings were arrived at using correlation and regression analysis.Findings: The findings show that students significantly overestimated their generic skill level in comparison to employer assessments. That the students are "unaware" of their lack of skill. The data also shows that this state of "unaware" correlates strongly with students’ lack of competence. It is more likely that the less-skilled students will not know. Consequently, there is a problem of students being "unskilled and unaware" in Malaysia.Novelty/Implications: This research sheds light on why there has been a rise in graduate unemployment in Malaysia, namely, that recent grads lack the necessary skills and experience to find gainful employment.